Europium oxide nanoparticles (EONP) enhance the cryoprotective effects of chilled rabbit semen preservation via antioxidant and mitochondrial enhancement - Alfattah, Mohammed A. (Frontiers in Veterinary Science, 2026)
IntroductionThis study investigated the cryoprotective effects of europium oxide nanoparticles [nanozymes; Europium oxide nanoparticles (EONP)] on rabbit sperm quality during 72 h of chilled storage at 4 °C due to its robust antioxidant ability (mimicking enzymes) and mitochondrial enhancer.MethodsIn this experiment, diluted semen samples were treated with different concentrations of EONP: 0 (EONP0), 25 (EONP25), 50 (EONP50), or 100 (EONP100) ng/ml. The treated samples were then stored at 4 °C for three days. Sperm quality attributes such as viability, motility, membrane integrity, and morphology were measured at 24, 48, and 72 h of storage. Oxidative/antioxidant activities and mitochondrial enzyme levels were also assessed after 72 h of storage.ResultsThe results show a quadratic relationship between EONP supplementation (at 25 or 50 ng/ml) and improved sperm motility, viability, and membrane integrity at all time points observed (P < 0.01). Additionally, a dose-dependent relationship was found between EONP levels and the concentrations of GPx, CAT, and SOD. In contrast, all groups supplemented with EONP showed a significant decrease in malondialdehyde (MDA), protein carbonyl (PC), hydrogen peroxide (H2O2), and nitric oxide (NO) levels compared to the extender without EONP (P < 0.001). The activities of succinate dehydrogenase (SD), malate dehydrogenase (MD), citrate synthase (CS), and ATP showed significant and quadratic improvements at EONP concentrations of 50 and 100 ng/ml compared to the 25 ng/ml concentration. Principal component analysis 1 (PCA1) was positively correlated with EONP supplementation, antioxidant markers, mitochondrial enzyme activities, and sperm quality parameters. Principal component analysis 2 (PCA2) showed a negative association between different EONP concentrations (0, 25, 50, and 100 ng/ml) and oxidative markers and sperm abnormalities after 72 h of preservation at 4 °C.DiscussionNanozyme supplementation of rabbit semen extenders significantly improves sperm quality during 72-h chilled storage by increasing antioxidant competence, reducing oxidative stress (OS), and boosting mitochondrial enzyme activity. Our data suggest that europium oxide nanoparticles are a promising additive for chilled rabbit semen preservation, with implications for artificial insemination (AI) and rabbit breeding.